Does skill specialisation influence individual differences in drag flicking speed and accuracy?. Issue 6 (19th March 2017) - Rosalie, Simon M.; McIntyre, Andrew S.; Stockman, Stacey; King, Craig; Watkins, Cameron; Wild, Catherine Yvette; Ng, Leo
ABSTRACT: Research has revealed that individual soccer goalkeepers respond differently to penalty shots, depending on their specific perceptual and motor capabilities. However, it remains unclear whether analogous differences exist between individual penalty takers, and if specialising in penalty taking affects the occurrence of differences between individuals. The present study examined individual differences in penalty shot speed and accuracy for specialists in penalty taking versus non-specialists. Expert specialist field hockey drag flickers and equivalently skilled non-specialists performed drag flicks towards predetermined targets placed in the face of a standard field hockey goal. Comparisons in shot speed and accuracy were made at a group level (specialists vs. non-specialists) as well as between individuals. Results revealed differences in both speed and accuracy between specialists, but only differences in speed between non-specialists. Specialists generated significantly greater shot speed than non-specialists ( P < .001) and were more accurate to some, but not all, targets (top left, P < .006, bottom left P < .001). In addition, it was found that in specialists increasing practice correlated with decreasing accuracy. This may indicate that excessive practice could potentially reduce a specialist's accuracy in shooting towards specific targets.